A Surgeon-Centered Neuromuscular Block Protocol Improving Intraoperative Neuromonitoring Outcome of Thyroid Surgery - Lu, I-Cheng; Hsu, Chiung-Dan; Chang, Pi-Ying; Wu, Sheng-Hua; Huang, Tzu-Yen; Lin, Yi-Chu; Ko, How-Yun; Dionigi, Gianlorenzo; Chai, Young Jun; Chiang, Feng-Yu; Kuo, Yi-Wei; Wu, Che-Wei (Frontiers in Endocrinology, 2022)
Background Neuromuscular blocking agents provide muscular relaxation for tracheal intubation and surgery. However, the degree of neuromuscular block may disturb neuromuscular transmission and lead to weak electromyography during intraoperative neuromonitoring. This study aimed to investigate a surgeon-friendly neuromuscular block degree titrated sugammadex protocol to maintain both intraoperative neuromonitoring quality and surgical relaxation during thyroid surgery. Methods A total of 116 patients were enrolled into two groups and underwent elective thyroid surgery with intraoperative neuromonitoring. All patients followed a standardized intraoperative neuromonitoring protocol with continuous neuromuscular transmission monitoring and received 0.6 mg/kg rocuronium for tracheal intubation. Patients were allocated into two groups according to the degree of neuromuscular block when the anterior surface of the thyroid gland was exposed. The neuromuscular block degree was assessed by the train-of-four (TOF) count and ratio. Patients in group I received sugammadex 0.25 mg/kg for non-deep neuromuscular block degree (TOF count = 1 4). Patients in group II were administered sugammadex 0.5 mg/kg for deep neuromuscular block degree (TOF count = 0). The quality of the intraoperative neuromonitoring was measured using the V1 electromyography (EMG) amplitude. An amplitude less than 500 μV and greater than 500 μV was defined as weak and satisfactory, respectively. Results The quality of the intraoperative neuromonitoring was not different between groups I and II (satisfactory/weak: 75/1 vs. 38/2, P = 0.14). The quality of surgical relaxation was acceptable after sugammadex injection and showed no difference between groups [55/76 (72.3%) in group I vs. 33/40 (82.5%) in group II, P = 0.23]. Conclusions This surgeon-centered sugammadex protocol guided by neuromuscular block degree (0.5 mg/kg for deep block and 0.25 mg/kg for others) showed comparably high intraoperative neuromonitoring quality and adequate surgical relaxation. The results expanded the practicality of sugammadex for precise neuromuscular block management during monitored thyroidectomy.